Survival analysis of bank note circulation: Fitness, network structure and machine learning - Diego Rojas; Juan Estrada; Kim P. Huynh; David Tomás Jacho-Chávez (Bank of Canada, 2020)
The efficient distribution of bank notes is a first-order responsibility of central banks. We study the distribution patterns of bank notes with an administrative dataset from the Bank of Canada's Currency Information Management Strategy. The single note inspection procedure generates a sample of 900 million bank notes in which we can trace the length of the stay of a banknote in the market. We define the duration of the bank note circulation cycle as beginning on the date the note is first shipped by the Bank of Canada to a financial institution and ending when it is returned to the Bank of Canada. In addition, we provide information regarding where the bank note is shipped and later received, as well as the physical fitness of the bank note upon return to the Bank of Canada's distribution centres. K-prototype clustering classifies bank notes into types. A hazard model estimates the duration in circulation of bank notes based on their clusters and characteristics. An adaptive elastic net provides an algorithm for dimension reduction. It is found that while the distribution of the duration is affected by fitness measures, those effects are negligible when compared with the influence exerted by the clusters related to bank note denominations.
Keywords: E42; E51; C52; C65; C81; 330; Bank notes; Econometric and statistical methods; Payment clearing and settlement systems